2022
DOI: 10.3389/fvets.2022.899854
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological, Molecular, and Epidemiological Investigation of Cryptosporidium Infection Among Cattle and Buffalo Calves From Assiut Governorate, Upper Egypt: Current Status and Zoonotic Implications

Abstract: Details about the epidemiological patterns and real contributions of different reservoir animals in maintaining the transmission cycle of Cryptosporidium spp. in Upper Egypt remain lacking. This study was designed to investigate the occurrence of Cryptosporidium spp. in cattle and buffalo (n = 608) from Upper Egypt. The parasite for the resulting positive samples by fecal examination was molecularly identified using nested PCR targeting the small subunit rRNA. Moreover, several explanatory variables, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Molecular information on the investigated protist species is particularly scarce in Egyptian animal populations in general and dogs and cats in particular. The study expands and complements information already provided by our research team on the epidemiology of enteric protists of public veterinary relevance in livestock species including buffaloes, cattle, and dromedary camels ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 62%
“…Molecular information on the investigated protist species is particularly scarce in Egyptian animal populations in general and dogs and cats in particular. The study expands and complements information already provided by our research team on the epidemiology of enteric protists of public veterinary relevance in livestock species including buffaloes, cattle, and dromedary camels ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 62%
“…Cattle with diarrhea generally have higher rates of Cryptosporidium spp. infection [ 12 , 31 ]. Similarly, in this study, the infection rate of Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, Elmahallawy et al from Egypt reported that the female calves were more susceptible to Cryptosporidium spp. than males [ 54 ]. Therefore, the role of gender as a risk factor for Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%